Implementasi Filtrasi Sinyal Electrocardiogram (ECG) menggunakan metode Butterworth pada Android dengan Teknologi Edge Computing - Achmad Brahmantyo Arundaya Subianto; Adhitya Bhawiyuga; Dany Primanita Kartikasari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
In healthcare, a check-up that is done frequently is a heart rate checkup commonly known as Electrocardiogram (ECG). Using technology, this checkup can be done remotely and easily, by using a technology concept called Internet of Things. Before analyzing ECG data, the data must go through a step called pre-processing. This step is used to reduce noise in the ECG data so it is more recognized. If this pre-processing is done in the cloud, the amount of data from many patients will burden the cloud. To solve this issue, pre-processing will be done in the Edge of the network. This way, the cloud can focus its computation powers to save and analyze ECG data. A plausible pre-processing is data filtration, with a digital filter called Infinite Impulse Response (IIR). The Edge used in this system is an Android, Android has more computational power than a sensor device in IoT. The Android role is to be a gateway, Android will receive data from a sensor device with BLE protocol, process the data, then sends the data to the Cloud. The proposed system has a data transmission delay from the gateway to the Cloud, the delay averages about 784,6 miliseconds.